REGULARITIES IN CHANGING RHEOLOGICAL PROPERTIES OF SWELLING CLAYS (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
The present article focuses on the rheological properties of swelling clays. The test results show that the ratio liquefaction coefficient and water-colloidal fraction independently of soil physical state (density, moisture) is a constant quality.